THE EFFECT OF ORGANIZATIONAL COMMITMENT, MOTIVATION AND JOB SATISFACTION ON THE PERFORMANCE OF CERTIFIED LECTURERS - Nursaimatussaddiya, Nursaimatussaddiya; Cai Cen, Cia; Purnama Sari, Dian; Habibie, Muhammad; Astrid Anindya, Desy (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
The research aims to analyze the effect of organizational commitment on the performance of certified lecturers at the Bina Karya High School of Economics, to analyze the effect of work motivation on performance, to analyze the effect of job satisfaction on performance, to analyze what factors are more dominant in influencing performance. The location or place of research is the Bina Karya College of Economics located on Jalan Diponegoro Tebing Tinggi Sumatra Partially the organizational commitment variable has a positive and significant effect on the performance variable of the lecturer at the Bina Karya College of Economics. Partially, the motivation variable has no significant effect on the performance of the Bina Karya College of Economics lecturers, Partially, the job satisfaction variable has a positive and significant effect on the performance of the Bina Karya College of Economics lecturers' performance. Simultaneously, organizational commitment, motivation, and job satisfaction have a positive and positive effect. significantly to the performance of the lecturers of the Bina Karya College of Economics. The R2 value obtained is 0.681 or 68.1% which shows the variables of Organizational Commitment, Motivation and Job Satisfaction in explaining the variations that occur in the performance of the lecturers of the Bina Karya High School of Economics 68.1 %, while the remaining 31.9% is explained by other variables not included in the model such as compensation, facilities, organizational culture, and others.